INFLUENCE OF THE MECHANICAL-PROPERTIES OF THE DISPERSED PHASE UPON THE BEHAVIOR OF NYLON RUBBER BLENDS - CROSS-LINKING EFFECT - SEO, YS; HWANG, SS; KIM, KU; LEE, JW; HONG, SI (ELSEVIER SCI LTD, 1993)
Rubber-modified polyamides were obtained directly by blending modified poly(styrene-b-butadiene-styrene) (SBS) triblock copolymer used as the rubbery component and nylon 6. The rubber was modified with various amounts of maleic anhydride (MA) with the aid of dicumyl peroxide. In this study, the influence of MA concentration on the crosslinking level of the rubber and its effect on the blend properties were investigated. Crosslinking level of MA-modified SBS was measured using isooctane, the calculation being done following the Flory-Rehner equation. Impact testing of the blends revealed a maximum peak in impact strength versus rubber crosslinking level. However, the maximum was not so eminent as we expected. Explanations about the impact behaviour of the blends related to toughening mechanisms are presented.
Keywords: IMPACT